What happened to Glenn Greenwald? Trump happened – and put the left’s priorities to the test (Jonathan Cook's Blog, 2021)
By fixating on Trump, elements of the left have drifted into worryingly authoritarian ways of thinking – sometimes openly, more often implicitly – as a bulwark against the return of Trump or anyone like him.